Exploring Audience Perceptions of, and Preferences for, Online News Videos. (4th July 2021) - Koliska, Michael; Thurman, Neil; Stares, Sally; Kunert, Jessica
ABSTRACT: Journalism professionals and media experts have traditionally used normatively formed criteria to evaluate news quality. Although the digital news media environment has enabled journalists to respond at unprecedented speed to audience consumption patterns, little academic research has systematically addressed how audiences themselves perceive and evaluate news, and even less has focused on audio-visual news. To help fill this research gap, we conducted in-depth group interviews with 22 online news video consumers in the UK to explore their perceptions of online news videos—an increasingly popular news format. Thematic analyses suggest audiences evaluate online news videos using a complex and interwoven set of criteria, which we group under four headings: antecedents of perceptions, emotional impacts, news and editorial values and production characteristics . Some of these criteria can be positioned clearly in relation to the literature on news quality in general, while our documentation of the others contributes new, format-specific knowledge. Our findings offer journalists practical insights into how audiences perceive and evaluate a host of characteristics of online news videos, while our conceptual framework provides a foundation for further academic research on audience evaluations of online news videos, and even audio-visual news more generally.